2015
DOI: 10.1002/app.41900
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of graft copolymer from dealkaline lignin and styrene

Abstract: Graft copolymerization of styrene onto dealkaline lignin by ferrous chloride and hydrogen peroxide coinitiator has been achieved successfully. The influence of temperature and reaction time as well as the amount of the styrene monomer, initiator, and catalyst on the grafting copolymerization was investigated. The optimum reaction conditions were determined as follows: c (styrene) 5 20.00 mmol, c (H 2 O 2 ) 5 5.00 mmol, c (FeCl 2 ) 5 0.10 mmol, T 5 30 C and t 5 48 h. The optimum yield (Y), total conversion (TC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…These grafted copolymers exhibited some impressive properties, such as thermal resistance and UV absorption, which could find potential applications such as compatibilizers for the blends of thermoplastic materials and UV blockers for biocomposites . Currently, the graft copolymerization reaction between lignin and vinyl monomers has been proved to be successfully initiated by FeCl 2 –H 2 O 2 , K 2 S 2 O 8 –NaS 2 O 3 , H 2 O 2 , and K 2 S 2 O 8 –(NH 4 ) 2 Fe (SO 4 ) 2 ·6H 2 O. ,, However, the homopolymers normally form during the graft copolymerization reaction. Based on the previous reports published by others and us, it is worth emphasizing that the calcium chloride–hydrogen peroxide (CaCl 2 –H 2 O 2 ) initiator system exhibits a highly selective method for grafting acrylic monomer onto lignin.…”
Section: Introductionmentioning
confidence: 99%
“…These grafted copolymers exhibited some impressive properties, such as thermal resistance and UV absorption, which could find potential applications such as compatibilizers for the blends of thermoplastic materials and UV blockers for biocomposites . Currently, the graft copolymerization reaction between lignin and vinyl monomers has been proved to be successfully initiated by FeCl 2 –H 2 O 2 , K 2 S 2 O 8 –NaS 2 O 3 , H 2 O 2 , and K 2 S 2 O 8 –(NH 4 ) 2 Fe (SO 4 ) 2 ·6H 2 O. ,, However, the homopolymers normally form during the graft copolymerization reaction. Based on the previous reports published by others and us, it is worth emphasizing that the calcium chloride–hydrogen peroxide (CaCl 2 –H 2 O 2 ) initiator system exhibits a highly selective method for grafting acrylic monomer onto lignin.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last few decades, for different purposes, the synthesis of lignin-based graing copolymers has been carried out mainly by free-radical polymerization (FRP). [10][11][12][13][14][15][16][17][18][19] However, along with the atom transfer radical polymerization (ATRP) was rst developed by Sawamoto and Matyjaszewski et al, 20,21 it has previously been utilized for "graing from" processes of graing copolymerization from lignin. [22][23][24][25][26][27] ATRP, as an especially powerful "living"/controlled free-radical polymerization (LCFRP), has emerged as one of the most robust and versatile synthetic techniques in lignin graing copolymerization.…”
Section: Introductionmentioning
confidence: 99%
“…31 Then it is further explored by Ying et al with IE of 1.80 and a up to 7.23 through introducing polyurethane grafting segments. 36 All of the works have demonstrated that protein imprinted hydrogel is a promising material for the selective adsorption and separation of protein. The results presented in this article takes the advantaged of PEG, a water-soluble polymer with biocompatibility and low toxicity, in forming alginatebased hydrogel with lower SD.…”
Section: Rebinding Specificitymentioning
confidence: 99%